How to Create Brand Evangelists: A Conceptual Framework - Purwandani, Meirissa; Widodo, Arry; Silvianita, Anita; Rubiyanti, Nurafni (Journal of International Conference Proceedings, 2023)
This study aims to investigate the relationship between brand personality, brand symbolism, self-expressiveness, affective commitment, and brand trust on brand evangelism using data from Telkom University Bandung students. The research model used is structural equation modeling (SEM) with a partial least square (PLS) approach. The results showed that brand trust and affective commitment are the most important antecedents of brand evangelism, followed by brand personality, self-expressiveness, and brand symbolism. Brand trust acts as a mediating variable between brand personality, brand symbolism, self-expressiveness, and affective commitment with brand evangelism. This research has several implications for companies in building brand evangelism. Companies need to build a strong brand personality, use the right symbols, increase self-expressiveness, and build strong emotional relationships with consumers.